Geomechanical evaluation of shale caprock integrity for effective carbon storage - Nur Najwa Syuhada, Suhaidi; Norida, Ridzuan; Norasyikin, Ismail (Society of Petroleum Engineers, 2025)
This study analyze the geomechanical behavior of shale cap rocks during CO2 injection for Carbon, Capture and Storage (CCS) and specifically, the mechanisms of rock failure. It compares shale properties of two major CO2 storage sites of the United States (Shale 1 & Shale 2) with a local Malaysian shale formation (Shale 3). The findings are intended to improve the understanding of caprock security and risk reduction in order to achieve safer storage methods. The shale samples (Shale 1, Shale 2, and Shale 3) were characterized for their mineralogical and morphology features by FESEM and EDX analysis. TGA were conducted to study thermal stability and triaxial compression tests were carried to evaluate the mechanical properties. A reservoir model was developed in tNavigator reservoir simulator to simulate CO2 injection behavior in the local Malaysian shale (Shale 3), and results were compared with literature data from two U.S. formations (Shale 1 & 2) with successful CCS project. Mineralogical investigation showed quartz as the major mineral in all the shale samples while the amount of clay and organic matter varied. Regarding the FESEM imaging, Shale 1 and Shale 2 were of lower porosity which was due to higher content of quartz in these shales. EDX analysis identified elevated calcium and oxygen concentrations in Shale 1 and Shale 2, suggesting differing geochemical properties from Shale 3. The TGA showed thermal decomposition of all samples at approximately 650°C, with Shale 3 exhibiting superior thermal stability which could help to maintain structural integrity under thermal stresses pertaining to CCS. Mechanical properties of Shale 1 and Shale 2 were greater than those of Shale 3, as shown by the testing results. Reservoir simulation indicated that despite its different mineralogical properties, Shale 3 had comparable CO2 storage capacity to the other two samples. These findings suggest that rock failure risks are influenced by both mechanical and geochemical interactions. This paper offers new insights into shale caprock failure mechanisms under CO2 injection, providing crucial data for optimizing CCS site selection and enhancing storage security, particularly in Malaysia. By combining experimental analysis with advanced reservoir simulation, the study contributes to the development of safer and more efficient CCS practices for long-term CO2 storage.